Autonomy of Nurses in Their Work and Associated Factors in Nurses of Selected Public Hospitals of Wollega Zones, Oromia Regional State, Western Parts of Ethiopia, 2020 - Mulisa D (Dove Medical Press, 2021)
Diriba Mulisa,1 Tadesse Tolossa,2 Misganu Teshoma Regasa,1 Lami Bayisa,1 Tesfaye Abera,1 Bizuneh Wakuma,3 Alemnesh Mosisa1 1School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 2Department of Public Health, Institutes of Health Sciences, Wollega University, Nekemte, Ethiopia; 3Department of Pediatric nursing, Institutes of Health Sciences, Wollega University, Nekemte, EthiopiaCorrespondence: Diriba MulisaSchool of Nursing and Midwifery, Institutes of Health Sciences, Wollega University, P.O.Box: 395, Nekemte, EthiopiaTel +251982725422Email diribamilisa@gmail.comBackground: Nursing clinical autonomy is a decision made by the nurse about individual patient care independently. The development of the nursing profession needs an increment in nurses’ autonomy in their work. Knowing the status of nursing autonomy and factors associated with it is recommended for developing nurses’ profession. The aim of this study was to getthe status of nursing autonomy and associated factors.Methods: An institution-based cross-sectional study was conducted among nurses working in selected public hospitals. For data entry, Epi Data version 3 was used and data was exported to Stata SE version 14 for analysis. To find the associated variables with the autonomy of nurses, bivariable and multivariable logistic regression methods were used. For this analysis, variables with a P-value of ≤ 0.25 were candidates for multiple logistic regressions. To get the final variables, backward logistic regression model was used. Variables with a P-value of ≤ 0.05 were considered as associated factors for the level of autonomy of nurses and the final finding was presented with a description, graph, and tables.Results: In this study, 349 nurses were involved in the study, and all have been participated and yielded a response rate of 100%. Greater than half of nurses were male 188 (53.87%). More proportion of the nurses have a working experience of less than six years (214 (61.32%)). Again, more proportion of nurses have not engaged in training focusing on the nursing profession (208 (59.60%)). Greater than half of the nurses in this study have a poor level of autonomy regarding their work in the field of nursing profession (188 (53.87%)). Factors contributing to a low level of autonomy among nurses are being older AOR= 0.58 (95% CI 0.35, 0.98) and not participate in a member of nurses’ association AOR =0.29 (95% CI 0.14, 0.61). Again, the finding showed that nurses who wish to stay in the nursing profession have a high level of nursing autonomy AOR=1.82, (95% CI 1.09, 3.02).Conclusion and Recommendation: Nurses’ autonomy regarding their work is very low in the study area. Being relatively older, not participating in any nursing association, and having the intent to stay in the nursing profession are factors that affect nursing autonomy in their work. These contributing factors have to be identified and improved by concerned stakeholders in the health care system to improve nurses’ autonomy in their works.Keywords: autonomy, nursing, profession, Ethiopia